1991
DOI: 10.2500/108854191778879197
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Immune Responses to Food Antigens in Neonates and Infants

Abstract: Normal newborns regularly form circulating antibodies to milk proteins by LOto 14 days of life. Concentrations of these antibodies are influenced by gestational age but not by passive maternal antibody. Secretory antibodies of the 19A and 19M-isotype directed against casein and (3-lactoglobulin are present in the saliva of normal neonates. SlgA-anti-casein is higher in saliva of newborns at risk to develop atopic disease. (Allergy Proc 12, 5: 309-312, 1991.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…If anything, supplementation with L. acidophilus LAVRI-A1 was associated with lower IgA production, although this was not statistically significant. Consistent with other reports [8,27], this study also demonstrated that the development of allergic sensitization was associated with higher total IgA levels, as noted in the placebo group (P = 0.021) at 6 months of age. The reasons for this are unclear, but it is of note that a key environmental 'risk factor' for allergic disease, namely early introduction of solid food, was also associated with increased IgA levels.…”
Section: Discussionsupporting
confidence: 93%
“…If anything, supplementation with L. acidophilus LAVRI-A1 was associated with lower IgA production, although this was not statistically significant. Consistent with other reports [8,27], this study also demonstrated that the development of allergic sensitization was associated with higher total IgA levels, as noted in the placebo group (P = 0.021) at 6 months of age. The reasons for this are unclear, but it is of note that a key environmental 'risk factor' for allergic disease, namely early introduction of solid food, was also associated with increased IgA levels.…”
Section: Discussionsupporting
confidence: 93%
“…The gastrointestinal absorption of antigenically intact dietary proteins is more extensive during the first days of life, and antibodies to milk proteins can be detected in the serum of neonates [22]. Sensitive methods allow even the detection of antidietary antibodies at low titre in normal subjects [23].…”
Section: Measurement Of Iga and Igg Activity To Non-dietary Antigensmentioning
confidence: 99%
“…The present paper is a follow-up study of a previously published investigation on secretory. immunity against cow's milk protein in neonates at risk of allergy (4, 5).…”
mentioning
confidence: 99%